AB0230 Centromere Pattern Exhibits A Specific Distribution of Titers among Anti-Nuclear Antibodies (ANAS) and Characterizes A Distinct Subset in Rheumatoid Arthritis. (15th July 2016) - Kuramoto, N.; Terao, C.; Ohmura, K.; Ikari, K.; Furu, M.; Yamakawa, N.; Yano, K.; Hashimoto, M.; Ito, H.; Fujii, T.; Murakami, K.; Sasai, R.; et al.
Abstract : Objectives: Centromere pattern is a staining pattern of anti-nuclear antibodies (ANAs). Here, we characterize the titer distribution of centromere pattern and analyze clinical and genetic features of centromere pattern-positive rheumatoid arthritis (RA). Methods: We examined ANA by indirect immunofluorescence for 9, 575 healthy volunteers and 1, 211 RA patients without systemic sclerosis in Kyoto University Hospital. HLA-DRB1 was genotyped for 285 RA patients. We compared distributions of titers among ANA and analyzed associations between centromere pattern and clinical or genetic features in the subjects. For validation, we recruited another cohort of 2, 424 RA patients in Tokyo Woman's Medical University Hospital to confirm the associations between centromere pattern and clinical features. Results: Eighty seven healthy volunteers (0.91%) and 25 RA patients (2.76%) were positive for centromere pattern of ANA. Centromere pattern was the only ANA staining pattern that demonstrated a definite bimodal distribution of levels in both healthy volunteers and patients with RA. Centromere pattern showed significantly higher levels than the other ANA patterns in the subjects positive for each ANA (p<0.0001). Centromere pattern-positivity was associated with old age and females in both healthy population and patients with RA. Centromere pattern-positive patients with RA showed lower positivity of rheumatoid factor (RF) (p=0.0011) that is one of risk factors for bone destruction. Centromere pattern was associated with Raynaud's phenomenon and complication of Sjögren's syndrome and primary biliary cirrhosis (p≤0.0052). No HLA-DRB1 alleles were significantly associated with centromere pattern. In validation study, 82 RA patients (2.41%) were positive for centromere pattern. Centromere pattern-positivity was again associated with old age, females and negativity of RF (p≤0.0044). Information of complications and symptoms was not available in the replication cohort. Centromere pattern-positive patients tended to show higher Total Sharp Score in spite of lower frequencies of RF in both cohorts. Conclusions: Centromere pattern showed a specific distribution of levels among ANA. Centromere pattern-positive RA is a distinct subset with specific clinical features and complications. Centromere pattern is a possibly new risk factor of bone destruction in RA. Disclosure of Interest: None declared